Aspectul controversat al hristologiei lui Ellen G. White - Zoltán Szallós-Farkas (TheoRhēma, 2017)
The controversial aspects that have long been debated in both specialist and lay circles of Seventh-day Adventism with regard to Ellen G. White’s Christology are the main issue in this article. We argue that White’s Christology presents the incarnate Christ’s human nature as being, paradoxically, both affected and unaffected by Adam’s Fall. It was affected by the Fall given the fact that Christ inherited, by his human birth, the innocent physical, volitional and psychological effects of Adam’s sin. White called these effects of Adam’s sin infirmities and weaknesses, which she took to be innocent, such as: hunger, thirst, tiredness, sadness, vulnerability to temptations and death. And, at the same time, White contended that the human nature of Jesus of Nazareth was absolutely sinless, both ontologically and ethically. Such a paradox, White justified by the biblical term monogenēs, “one of a kind,” meaning that Christ’s human nature was and still is an absolutely unique phenomenon in all of God’s creation. Christ had to be unique, in her view, because of his being God’s solution to the universal problem of sin and the Fall.